IDENTIFICATION AND QUANTIFICATION OF BETA-SITOSTEROL IN LEUCAS ASPERA LINN. BY HPTLC-MS - PRASHANT HANDE,; B S AJITKUMAR,; SHAILENDRA RANE,; MANISH HATE,; AKSHAY CHAREGAONKAR, (International Journal of Pharma and Bio Sciences, 2015)
Leucas aspera linn. is commonly called as ‘Pandharpheda’ and is widely distributed throughout south India, having many medicinal properties. A sensitive, simple and accurate HPTLC method has been established for identification and quantification of beta-sitosterol from leucas aspera linn. whole plant powder. Quantification was carried out on pre-coated plate of HPTLC silica gel 60 F254 using mobile phase (toluene: ethyl acetate: formic acid, 12:7:1,v/v/v). CAMAG scanner IV set at visible light (520nm) for detection and quantification. The percentage concentrations of the beta-sitosterol were found to be 0.0672.Response was linear over the range of 0.1µg to 0.5µg with 0.66 and 0.314 of %CV respectively.CAMAG TLC-MS interface was used for the confirmation of m/z values of beta-sitosterol in standard as well as sample. The m/z value was found to be 397(M+H+-H2O). The method i.e. HPTLC and TLC-MS together provides a rapid and secure method for detection, identification and quantification of biomarker beta-sitosterol.